Aboveground Forest Carbon Stock in Protected Area: A Case Study of Bukit Tigapuluh National Park, Indonesia - Arief Darmawan; Zulfira Warta; Elis Molidena; Alexandra Valla; Muhammad Iqbal Firdaus; Gunardi Djoko Winarno; Bondan Winarno; Teddy Rusolono; Satoshi Tsuyuki (Universitas Gadjah Mada, 2022)
The role of protected areas has been expanded into climate change mitigation, specifically on Reducing Emissions from Deforestation and Forest Degradation (REDD+). A reliable and practical method for measuring, reporting and verifying carbon stock is an essential component for REDD+. This study aims to recognize the characteristic and estimate aboveground forest carbon (AGC) stock in the tropical protected tropical area using a combination of terrestrial forest inventory and spatial data. A 168 cluster plots totaling 33.6 hectares were taken proportionally based on the percentage of forest cover types (dryland primary natural forest/DPF and dryland secondary natural forest/DSF) using a traditional forest inventory method (more than 5 cm dbh). Results showed that Bukit Tigapuluh National Park secured a significant AGC stock which has been estimated to be 269.2 [247.07; 291.43] tC/ha or 35,823,639 [32,872,312; 38,774,966] tC in total, being stored in approximately 133,051 hectares of the tropical rain forest. This result was higher than other studies in non-protected areas but slightly lower than other studies within protected areas. This finding supported the argument that protected areas possess a higher figure of AGC stock than other forest management units. The high amount of forest carbon biomass in the protected areas shall be very important assets for conducting the role of conservation for REDD+.